Potential emissions savings of lightweight composite aircraft components evaluated through life cycle assessment (eXPRESS Polymer Letters)
A cradle-to-grave life cycle assessment (LCA) of structural aircraft materials has been utilised to assess and compare the total emissions produced during manufacturing, use and disposal of aerospace materials and their selected components. First, a comparison of aluminium, GLARE and carbon fibre reinforced polymer (CFRP) plates was performed to investigate the potential of lightweight composites in reducing aviation emissions. Subsequently, a case study is presented on a tubular component for which more accurate manufacturing data were directly available. A structural steel tube was replaced with a composite tubular component. The analysis has shown that once the composite material is used as a component in the aircraft, there is a cumulative saving of aircraft fuel and emissions, in particular from CFRP structures. The environmental analysis included the long-term use predictions for CFRPs, involving detailed raw materials production, use and operation, and disposal scenarios.